The Effect Of Secang The Effect of Secang (Caesalpinia sappan) Masks on the Healing of Acne (Acne vulgaris) in Women Aged 21–25 Years Old - Maasyitoh Sari Latifah (Jurnal Biosains Pascasarjana, 2023)
Introduction: Acne can be caused by the presence of acne-causing bacteria. Currently, various studies of acne treatment with herbal ingredients both topically and orally have been carried out with the aim of reducing acne-causing bacteria. Several studies have shown that the active compound of Secang, namely brazilin extracted with methanol and 50% ethanol in Propionibacterium acnes, has been shown to have anti-bacterial, lipase inhibitor, and antioxidant activity. So that researchers are interested in conducting research on "The Effect of a Secang Mask (Caesalpinia sappan) on Healing Acne (Acne vulgaris) in Women Aged 21-25 Years". Material and Methods: This type of research is a paired numerical comparative analytical study using experimental methods and data collection methods with repeated measurements of Pretest-Posttest Control Group Design. 15 samples with acne were examined before given Secang mask with a composition of 0.5 grams of secang extract and 9.5 grams of rice flour. data was taken every 2 weeks for 4 weeks. The research data obtained will be presented in tabular form and then tested with the T-test in analyzing the results of the differences between pre-test and post-test Results: Based on the results of the study the effect of a secang mask (Caesalpinia sappan) on the healing of acne (Acne vulgaris) in women aged 21-25 years which was carried out for 30 days with a frequency of once every 2 days showed a significant decrease in the average total number of acne lesions (p = 0.00) compared to posttest, with a mean decrease of 33.38. Conclusion: From these statistical results, it can be concluded that secang mask therapy can improve acne healing in women aged 21-25 years which is characterized by a decrease in the total number of acne lesions, both comedones and inflammatory acne.